TRANSFORMASI MOTIVASI BELAJAR MELALUI PEMBELAJARAN BERBASIS MATLAB : STUDI KUASI -EKSPERIMEN PADA SISWA - Ahmad Sofi Yullah; Siti Nur Azizah (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study aims to determine the effect of MATLAB-based learning on the motivation to learn of Grade 10 students in the polynomial unit at MAN 2 Banyuwangi. The method used was a quasi-experimental design (Non-equivalent Control Group Design) consisting of an experimental class and a control class. Motivation questionnaires, observations, and documentation were used to collect data, which was then analysed using a t-test. The results indicate that learning motivation in the experimental group was higher (83.00–86.00) compared to the control group (83.00–85.00). Statistical testing revealed a significant p-value (p < 0.05). The research results indicate that MATLAB-based learning is more effective than conventional learning. Based on the t-test results, the t-value was 3.55, and the p-value was 0.01, indicating a significant difference between the two groups. The study concludes that interactive visualisation, dynamic simulations, and student engagement in mathematics learning through MATLAB can enhance students’ learning motivation